Теория сохранения книжных памятников в составе библиотечных фондов. Историография и современное состояние проблемы (Библиосфера)
The historiographical review of rare books conservation theory in library collections is given. The question of the interdisciplinary character of the problem is put, and therefore library science, legal, archeographical aspects of the problem of rare books preservation are considered. The development of terms preservation, conservation, fund hygiene is analyzed.